FEATURES OF THE COMMUNICATIVE COMPETENCE OF THE FUTURE DOCTOR - Sagiraev Nodir Jumakulovich; Ahmadaliev Sirojidin Mamasidikovich (Scholar Express Journals, 2021)
Communicative competence is an important part of professional training of subject-subject type of activity to which it belongs and the medical profession. In the context of modern medical education to improve the problem of finding psychologically based direction of the communicative competence of medical students appears to be very relevant. The better formed, the future of doctore is professionally important qualities, the better his communication with patients.
Keywords: Medical Education; Communicative Competence; Future Doctor; Profession